9-Valent HPV vaccine for cancers, pre-cancers and genital warts related to HPV. (2nd November 2015) - Pitisuttithum, Punnee; Velicer, Christine; Luxembourg, Alain
Abstract : Human papillomavirus (HPV) is the causative agent of nearly all cervical cancer cases as well as a substantial proportion of anal, vulvar, vaginal, penile and oropharyngeal cancers, making it responsible for approximately 5% of the global cancer burden. The first-generation HPV vaccines that is, quadrivalent HPV type 6/11/16/18 vaccine and bivalent HPV type 16/18 vaccine were licensed in 2006 and 2007, respectively. A second-generation 9-valent HPV type 6/11/16/18/31/33/45/52/58 vaccine with broader cancer coverage was initiated even before the first vaccines were approved. By preventing HPV infection and disease due to HPV31/33/45/52/58, the 9vHPV vaccine has the potential to increase prevention of cervical cancer from 70 to 90%. In addition, the 9vHPV vaccine has the potential to prevent 85–95% of HPV-related vulvar, vaginal and anal cancers. Overall, the 9vHPV vaccine addresses a significant unmet medical need, although further health economics and implementation research is needed.